A dataset of Vietnamese university lecturers' teaching skills: A TPACK model - Hieu, Hoc Le; Thanh, Hai Pham Thi; Luong, Dinh-Hai (Data in brief, 2024)
The dataset described Vietnamese university lecturers’ teaching and was constructed using elements of the TPACK model. According to the model of Mishra and Koehler [1], the questionnaire was developed. It was delivered through online platforms. The data collection period was three weeks, from February 6 to February 24, 2024. The survey was conducted using the snowball sampling method, with 503 participants. The article analyzed the remaining 461 records after excluding 41 invalid ones. The dataset was referenced in the Mendeley Data repository [10]. University lecturers could use the data set to enhance their personal professional development. In addition, the dataset could assist higher education institutions in formulating plans and training programs, instruct teaching staff, and assist educational managers and policymakers in formulating policies that encourage technology integration in teaching, thereby enhancing the quality of education.